Clinical and epidemiological characterization of abortions in adolescents, Dr Israel Ranuarez Balza Guárico State Hospital, 2013. (Revista Venezolana de Salud Pública, 2018)
Abortion in adolescents is a public health problem, because the complications arising from its practice are the main cause of death from 10 to 19 years, taking place under conditions that threaten the life, health and integrity of women. In the present investigation, the objective was to characterize clinically and epidemiologically abortions in adolescents seen in the Dr. Israel Ranuarez Balza" Hospital of the Guárico State during 2013. The methodology was a cross-sectional descriptive investigation.
Keywords: Abortion; adolescents; complications; clinic; Venezuela